Structural phase transitions in trigonal Selenium induce the formation of a disordered phase. (29th September 2015) - Pal, Anirban; Gohil, Smita; Sengupta, Surajit; Poswal, H K; Sharma, Surinder M; Ghosh, Shankar; Ayyub, Pushan
Abstract: Arguments based on the Mermin–Wagner theorem suggest that the quasi-1D trigonal phase of Se should be unstable against long wavelength perturbations. Consisting of parallel Se–Se chains, this essentially fragile solid undergoes a partial transition to a monoclinic structure (consisting of 8-membered rings) at low temperatures (≈50 K), and to a distorted trigonal phase at moderate pressures (≈3GPa). Experimental investigations on sub-millimeter-sized single crystals provide clear evidence that these transitions occur via a novel and counter-intuitive route. This involves the reversible formation of an intermediate, disordered structure that appears as a minority phase with increasing pressure as well as with decreasing temperature. The formation of the disordered state is indicated by: (a) a 'Boson-peak' that appears at low temperatures in the specific heat and resonance Raman data, and (b) a decrease in the intensity of Raman lines over a relatively narrow pressure range. We complement the experimental results with a phenomenological model that illustrates how a first order structural transition may lead to disorder. Interestingly, nanocrystals of trigonal Se do not undergo any structural transition in the parameter space studied; neither do they exhibit signs of disorder, further underlining the role of disorder in this type of structural transition.